CHARACERISTICS OF SEA HORSE Hippocampus comes FROM NORTH WATERS OF BINTAN ISLAND, RIAU ISLANDS - Evi Maya Sari; Mala Nurilmala; Asadatun Abdullah (COJ (Coastal and Ocean Journal), 2018)
Sea horse Hippocampus spp. is a group of unique marine biota and its distribution is spread all over the world. This study aims to determine the characteristics of seahorse Hippocampus comes from North Bintan waters by looking at the yield and degree of hydrolysis (DH) of the protein hydrolyzate sample. This samples obtained from the catch of fishermen in the North Waters of Bintan Island. The analysis is the measurement of the yield and the degree of hydrolysis. The results obtained from the study that the horse of sea H. comes from the North waters of Bintan shows that the highest yield in the sea horse body is bone that is equal to 43.69%. This proves that the seahorse is one of the ingredients that can be utilized as a further processed dry feed such as in the manufacture of flour and dried products (such as ginseng). As for the degree of hydrolysis generated from the substrate of H. comes a sea horse protein derived from meat and bone have a high value compared to the substrate of sea horse bone meal. Key words: sea horse, yield, degree of hydrolysis, North Waters of Bintan Island